Personalisasi Dan Platform Pengajaran Digital (Blended Learning, Online Learning, Adaptive Learning) - Siti Hawa; Ishaq Ishaq; Rahmad Syah Putra; Amirul Haq Rd (At-Ta'lim : Media Informasi Pendidikan Islam, 2021)
Abstract: Personalize And Digital Teaching Platform (Mixed Learning, Online Learning, Adaptive Learning)This paper, entitled Personalization and Digital Teaching Platforms (Blended Learning, Online Learning, Adaptive Learning, etc.) has problems (1) How important is personalization in digital learning, (2) How is the relationship between personalization and various important elements in digital learning? The purposes of this paper are (1) To find out how important personalization is in digital learning, (2) To find out how personalization is related to various important elements in digital learning. The writing method used is descriptive qualitative method. Data collection techniques are documentation techniques and data processing techniques using qualitative descriptive techniques. The results show that personalization in digital learning is very important because it is a change in teaching methods and methods in accordance with advances in science and technology. Personalization is closely related to an important element in learning, namely the use of the internet as the main media in the e-learning model. Furthermore, the personalization system is carried out to increase the ability or absorption of students in the use of technology. Approaches that can be taken in personalizing digital learning include: Blended learning (a model or strategy which is basically a combination of the advantages of face-to-face and virtual learning), Online learning (Online learning is the result of learning delivered electronically with using computers and computer-based media), Adaptive learning (adaptive learning), adaptive mobile learning is a multi-media learning program that presents learning media with mobile devices and has the ability to adapt to the characteristics of user learning styles (student learning styles). Abstrak: Personalisasi Dan Platform Pengajaran Digital (Blended Learning, Online Learning, Adaptive Learning)Tulisan yang berjudul Personalisasi dan Platform Pengajaran Digital (Blended Learning, Online Learning, Adaptive Learning, dll) ini memiliki masalah (1) Bagaimana pentingnya personalisasi dalam pembelajaran digital, (2) Bagaimana keterkaitan antara personalisasi dengan berbagai elemen penting dalam pembelajaran digital? Tujuan tulisan ini adalah (1) Untuk mengetahui Bagaimana pentingnya personalisasi dalam pembelajaran digital, (2) Untuk mengetahui Bagaimana keterkaitan antara personalisasi dengan berbagai elemen penting dalam pembeljaran digital. Metode penulisan yang digunakan adalah metode deskritif kualitatif. Teknik pengumpulan datanya adalah teknik dokumentasi dan teknik pengolahan data menggunakan teknik deskriptif kualitatif. Hasil penelitian menunjukan bahwa personalisasi dalam pembelajaran digital sangat penting karena merupakan suatu perubahan dalam metode dan cara mengajar sesuai dengan kemajuan ilmu pengetahuan dan ilmu teknologi. Personalisasi sangat terkait dengan elemen penting dalam pembelajaran, yaitu pada pemanfaatan internet sebagai media utama dalam model pembelajaran e-learning. Selanjutnya, system personalisasi dilakukan untuk meningkatkan kemampuan atau daya serap siswa dalam penggunaan teknologi. Pendekatan yang dapat dilakukan dalam personalisasi pembelajaran digital antara lain seperti: Blended learning ( Model ataupun srategi yang pada dasarnya merupakan gabungan keunggulan pembelajaran yang dilakukan secara tatap muka dan  secara virtual), Online learning (Pembelajaran online merupakan hasil dari suatu pembelajaran yang disampaikan sacara elektronik dengan menggunakan computer dan media berbasis computer), Adaptive learning (pembelajaran adaptive), adaptive mobile learning adalah program multi media pembelajaran yang menyajikan media pembelajaran dengan perangkat bergerak dan memiliki kemampuan untuk menyesuaikan dengan karakteristik gaya belajar pengguna(student learning styles).